Functioning in patients with major depression treated with duloxetine or a selective serotonin reuptake inhibitor in East Asia - Novick D; Montgomery W; Haro JM; Moneta MV; Zhu G; Yue L; Hong J; Duenas H; Brugnoli R (Neuropsychiatric Disease and Treatment)
Diego Novick,1 William Montgomery,2 Josep Maria Haro,3 Maria Victoria Moneta,3 Gang Zhu,4 Li Yue,5 Jihyung Hong,6 Héctor Dueñas,7 Roberto Brugnoli8 1Eli Lilly and Company, Windlesham, Surrey, UK; 2Eli Lilly Australia Pty Ltd, West Ryde, NSW, Australia; 3Parc Sanitari Sant Joan de Déu, Fundació Sant Joan de Déu, CIBERSAM, Universitat de Barcelona, Barcelona, Spain; 4Department of Psychiatry, The First Affiliated Hospital of China Medical University, Shenyang, 5Lilly Suzhou Pharmaceutical Company, Ltd, Shanghai, People’s Republic of China; 6Department of Healthcare Management, Gachon University, Seongnam, South Korea; 7Eli Lilly de Mexico, Mexico City, Mexico; 8School of Medicine, Sapienza University of Rome, Rome, ItalyPurpose: To assess and compare the levels of functioning in patients with major depressive disorder treated with either duloxetine with a daily dose of ≤60 mg or a selective serotonin reuptake inhibitor (SSRI) as monotherapy for up to 6 months in a naturalistic setting in East Asia. In addition, this study examined the impact of painful physical symptoms (PPS) on the effects of these treatments.Patients and methods: Data for this post hoc analysis were taken from a 6-month prospective observational study involving 1,549 patients with major depressive disorder without sexual dysfunction. The present analysis focused on a subgroup of patients from East Asia (n=587). Functioning was measured using the Sheehan Disability Scale (SDS). Depression severity was assessed using the 16-item Quick Inventory of Depressive Symptomatology-Self Report. PPS were rated using the modified Somatic Symptom Inventory. A mixed model with repeated measures was fitted to compare the levels of functioning between duloxetine-treated (n=227) and SSRI-treated (n=225) patients, adjusting for baseline patient characteristics.Results: The mean SDS total score was similar between the two treatment cohorts (15.46 [standard deviation =6.11] in the duloxetine cohort and 16.36 [standard deviation =6.53] in the SSRI cohort, P=0.077) at baseline. Both descriptive and regression analyses confirmed improvement in functioning in both groups during follow-up, but duloxetine-treated patients achieved better functioning. At 24 weeks, the estimated mean SDS total score was 4.48 (standard error =0.80) in the duloxetine cohort, which was statistically significantly lower (ie, better functioning) than that of 6.76 (standard error =0.77) in the SSRI cohort (P<0.001). This treatment difference was more apparent in the subgroup of patients with PPS at baseline. Similar patterns were also observed for SDS subscores (work, social life, and family life).Conclusion: Depressed patients treated with duloxetine achieved better functioning compared to those treated with SSRIs. This treatment difference was mostly driven by patients with PPS at baseline.Keywords: depression, antidepressant, duloxetine, SSRI, functioning